2005
DOI: 10.1103/physrevb.71.153307
|View full text |Cite
|
Sign up to set email alerts
|

Hysteresis in the quantum Hall regimes in electron double quantum well structures

Abstract: We present in this paper experimental results on the transport hysteresis in electron double quantum well structures. Exploring the measurement technique of fixing the magnetic field and sweeping a front gate voltage (Vg), we are able to study the hysteresis by varying the top layer Landau level fillings while maintaining a relatively constant filling factor in the bottom layer, allowing us to tackle the question of the sign of Rxx(up)-Rxx(down), where Rxx(up) is the magnetoresistance when Vg is swept up and R… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
18
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 21 publications
6
18
0
Order By: Relevance
“…Experimental observations of hysteresis in the transport properties of two-dimensional electron gas (2DEG) made of single layer and double layer quantum well heterostructures used in the study of the integer and fractional quantum Hall effects have been widely reported [1][2][3][4][5][6][7]. In the double-layer structure, the origin of the hysteresis was attributed to a phase transition between oppositely polarized ground states localized in the different layers [1].…”
Section: Introductionmentioning
confidence: 99%
“…Experimental observations of hysteresis in the transport properties of two-dimensional electron gas (2DEG) made of single layer and double layer quantum well heterostructures used in the study of the integer and fractional quantum Hall effects have been widely reported [1][2][3][4][5][6][7]. In the double-layer structure, the origin of the hysteresis was attributed to a phase transition between oppositely polarized ground states localized in the different layers [1].…”
Section: Introductionmentioning
confidence: 99%
“…These hysteretic effects have been associated with a number of physical phenomena, including non-equilibrium charge distributions [3][4][5] , long-lived eddy currents [6][7][8][9] within the interior of the 2DES, first order phase transitions involving the electron spin [10][11][12][13][14][15] or pseudospin [16][17][18][19] degrees of freedom, and metastable orientations of the electron nematic phases at high Landau level occupancy 20 . In the majority of these experiments the behavior of the collective electron state was inferred from measurements of magnetoresistance, which was found to depend strongly on the sweep rate and direction of the magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…This growth direction is in contrast to the [0001] oriented GaN films that preferentially grow on c-plane sapphire. On r-plane sapphire, however, we find the growth direction of the nanowires is the same as the observed (11)(12)(13)(14)(15)(16)(17)(18)(19)(20) film growth, with relatively low in-plane lattice mismatches of 1.15% and 16%, leading to ordered, vertical growth.…”
Section: Accomplishmentmentioning
confidence: 62%
“…SEM and TEM analysis indicate that the large majority of nanowires share a common [11][12][13][14][15][16][17][18][19][20] growth direction and have aligned facets. Nanowires grown on the c-plane (0001) sapphire surface, which a previous study reported shared the same [11][12][13][14][15][16][17][18][19][20] growth direction, do not exhibit a high degree of ordering. This growth direction is in contrast to the [0001] oriented GaN films that preferentially grow on c-plane sapphire.…”
Section: Accomplishmentmentioning
confidence: 99%